Trend and influencing factors of low birth weight among newborns in Chongming District of Shanghai from 2008 to 2022 - SHI Aiyu; GU Tianyi; XU Yan; HUANG Yuhua; SUN Xiaolei (Shanghai yufang yixue)
ObjectiveTo analyze the trend and influencing factors of low birth weight (LBW) among newborns in Chongming District of Shanghai from 2008 to 2022, so as to provide references for the development of intervention measures reducing the rate of LBW.MethodsBirth surveillance data of Chongming District of Shanghai from 2008 to 2022 were collected and organized, and the annual percentage change (APC) of LBW was calculated by using Joinpoint 5.0.2 software for trend change analysis. Logistic regression analysis was used to analyze the influencing factors of LBW.ResultsThe overall incidence of LBW was 3.71% in Chongming District, Shanghai from 2008 to 2022. Joinpoint trend analysis showed that the incidence of LBW in Chongming District had an upward trend (APC=5.49%, 95%CI: 3.31%‒7.72%, P<0.001).Multivariate logistic regression analysis showed that preterm birth, multiple births, female infants, birth defects, first pregnancy, primiparity, and a young father age (<20 years) were risk factors for LBW in Chongming District. Among the term infants, female infants, birth defects, and first pregnancy were risk factors for LBW (P<0.05). Female infants, birth defects, first pregnancy, primiparity, advanced maternal age (≥35 years), and a young father age (<20 years) were risk factors in singleton neonates.ConclusionThe incidence of LBW among newborns is on the rise in Chongming District of Shanghai. Therefore, high risk groups need to be identified, and prenatal check-ups and pregnancy care should be strengthened to reduce the risk of neonatal LBW.